2016
DOI: 10.1017/s002185961500132x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in soil organic carbon stocks under 10-year conservation tillage on a Black soil in Northeast China

Abstract: SUMMARYBiased assessment of tillage impacts on soil organic carbon (SOC) sequestration are often associated with a lack of information on the initial level of SOC stocks. The present study reported the changes in SOC concentrations and stocks following 10-year different tillage practices relative to the initial SOC levels. The tillage trial included no tillage (NT), ridge tillage (RT) and mouldboard plough (MP) on a Black soil (Hapludolls) in Northeast China. Results showed that tillage, soil depth and time si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 45 publications
(91 reference statements)
1
7
0
1
Order By: Relevance
“…This suggests that turning the soil with inversion tillage and placing residue at a deeper depth compared to mixing in residues throughout the tilled soil layer does not lead to more SOC deeper in the profile with full tillage compared to no-till management. This is similar to other studies that have also failed to detect differences between these tillage types 2729,4951 . Furthermore, there have been studies that found significantly higher SOC stocks with no-till adoption compared to systems with tillage management, but no differences between inversion tillage and reduced tillage management that also mix residue into the topsoil without inversion 28 .…”
Section: Discussionsupporting
confidence: 92%
“…This suggests that turning the soil with inversion tillage and placing residue at a deeper depth compared to mixing in residues throughout the tilled soil layer does not lead to more SOC deeper in the profile with full tillage compared to no-till management. This is similar to other studies that have also failed to detect differences between these tillage types 2729,4951 . Furthermore, there have been studies that found significantly higher SOC stocks with no-till adoption compared to systems with tillage management, but no differences between inversion tillage and reduced tillage management that also mix residue into the topsoil without inversion 28 .…”
Section: Discussionsupporting
confidence: 92%
“…Statistical analyses were carried out using SPSS (version 11.5, SPSS Inc., Chicago, IL, USA), and the treatment means were compared using the least significant difference (LSD) test at a significance level of P<0.05 (Liang et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Prior to start of the field experiment, the site had been cultivated continuously by conventional agricultural management with monoculture maize and intensive deep tillage for more than 15 years. Other details about soil characteristics at this site are provided in Table 1 (Liang et al, 2016).…”
Section: Methodsmentioning
confidence: 99%